Structural and properties development of expanded austenite layers on AISI 316L after low temperature thermochemical treatments - Mridha, Shahjahan; Haruman, E.; Sudin, M. Bin; Triwiyanto, A.; Hussain, P. (Asian Network for Scientic Information, 2011)
Low temperature Thermochemical treatments in fluidized bed furnace involving nitriding, carburizing, and hybrid treating,sequential carburizing-nitriding, have been conducted in the present work with the aim to improve surface properties of AISI 316L. The resulting layer is expanded austenite which is responsible to the higher hardness and better wears properties. Characterization of this expanded austenite layers were performed including XRD analysis, SEM and SPM and microhardness indentation were used to reveal the characters of the produced thin layers. The study demonstrates that hybrid treating produced a thicker layer and higher surface hardness with gentle-drop hardness profile compared to the other treatments. This is caused by the presence of dual expanded austenite γC and γN compared to individual nitriding and carburizing which only produces a single layer. XRD patterns of treated surfaces showing the absence of nitride and carbide precipitates. SPM-c haracterization reveals that expanded austenite has densely packed morphology which is responsible to the hardness improvement as well as high wear resistant surfaces. Services